Improved operation and design of modular multi-level converters through harmonic injection - Elayeb, Salahedin (2019)
Modular multilevel converters (MMC), amongst all multi-level converters, have received signiﬁcant interest recently due to their modularity, capability, availability and excellent performance characteristics. The MMC can be scaled to very high voltage levels and power ratings while providing good power quality and the opportunity to operate with redundancy to enable high availability. Operation at high voltage levels and power rating requires a high number of submodules (SMs) each with its own capacitor assembly of significant size to store the required energy. The required energy storage and hence capacitor volume can be influenced and reduced using harmonic injection techniques employing either voltage and/or current injection. Approaches using 3rd harmonic voltage injection and 2nd harmonic current injection have been reported, but, the combination of the 3rd harmonic injection, i.e. voltage and/or current, and 2nd harmonic current together have not been fully explored (including the freedom to adjust the relative time displacements). This thesis evaluates the influence of the classical and phase shifted 3rd harmonic voltage and current injection in combination with the 2nd harmonic current on the energy storage requirements including energy pulsation reduction and SM capacitor sizing. Mathematical models are derived. The phase-shifted 3rd harmonic voltage injection concept is presented considering its influence on reducing the peak synthesised voltage and two possible methods are proposed utilising the reduced peak synthesised voltage. Increasing the output voltage at the MMC terminals using the phase-shifted 3rd harmonic is considered, and a lookup table method is presented allowing further increase of the output voltage and reducing the line current. Power losses are reduced since the AC voltage can be increased allowing a reduction in current with an appropriate transformer design. The influence of the reduced peak synthesised voltage is further investigated considering its impact on resizing the SM capacitor size by allowing higher voltage ripple. A new design is achieved using phase shifted 3rd harmonic voltage injection. The continuous mathematical models are validated using a model with a full representation of switching, and selected methods are then validated experimentally in the laboratory.